Discrimination in employment, religious symbols and the "actual knowledge" of the employer. Issue 2 (June 2019) - Akhtar, Zia
The Title VII of the US Civil Rights Act of 1964, 42 U.S.C. section 2000e, et seq., as amended ("Title VII"), prohibits employers with at least 15 employees (including private sector, state, and local government employers), as well as employment agencies, unions, and federal government agencies, from discriminating in employment based on race, color, religion, sex, or national origin. It also prohibits retaliation against persons who complain of discrimination or participate in an Equal Employment Opportunity investigation. The US Equal Employment Opportunity Commission (EEOC) is responsible for enforcing federal laws that prohibit workplace discrimination and it has intervened by the federal body to prevent religious discrimination by corporations which seem to be breaching the law by discriminating against their employees. In EEOC v. Abercrombie & Fitch 575 U.S. ____ (2015), the US Supreme Court held that a religious practice of an employee should be accommodated if it does not cause "undue hardship." The Court then formulated the principle that applicant does not have to show that the employer had "actual knowledge" of the applicant's need for accommodation. Instead, the Court held that "an applicant need only show that his need for an accommodation was a motivating factor in the employer's decision." This has given the scope to a Chapter VII definition that stops short of strict liability but binds the employer to facilitate the employee where religious symbols are concerned. This article reviews the recent case law on discrimination in the work place and the disparate treatment test interpreted by the Supreme Court in the framework of employment law for religious employees and argues that the employer's actual knowledge requirement depends upon the circumstances of each case.